STUDY OF PSYCHOPATHOLOGICAL MANIFESTATIONS OF WAR VETERANS - Asriyan, Elina; Gevorgyan , Davit (Modern Psychology, 2022)
In recent years the world has witnessed many armed conflicts, such as the war in Nagorno-Karabakh (Artsakh), the war in Ukraine and others. Along with the physical destruction of infrastructures, human casualties and other obvious consequences, the consequences of war include long-term psychological harm to the people directly or indirectly involved in the armed conflicts, and even to their family members. This article summarizes the results of a psychological study conducted among servicemen who participated in the second Artsakh War (2020). In particular, the degree of expression and combination of PTSD, symptoms of anxiety and depression were revealed. The research was conducted with 300 servicemen approximately 6 months after the end of the war. The obtained results allow us to conclude that a considerable majority of the servicemen had a pronounced degree of the above clinical manifestations, which is connected with a simultaneous effect of different factors. Another important practical conclusion is that the overwhelming majority of the conscripts had a clinical degree of anxiety, depression, or a combination thereof, which unequivocally points to their need for psychological support. It is also indicative that a high level of anxiety and depression is more typical for the group of non-injured soldiers, which might suggest that physical trauma alone is not a sufficient factor for psychological problems, and the absence of a combat wound cannot insure against psychological traumatization. The results point to the necessity of PTSD-oriented psychological assistance to servicemen with the obligatory involvement of non-injured persons.